Stroke Rate Increases Around the Time of Cancer Diagnosis - Wei, Yi-Chia; Chen, Kuan-Fu; Wu, Chia-Lun; Lee, Tay-Wey; Liu, Chi-Hung; Shyu, Yu-Chiau; Lin, Ching-Po (Frontiers in Neurology, 2019)
Objective: To test whether strokes increase around the time of cancer diagnosis, we comprehensively examined the correlations of cancer and stroke by employing a population-based cohort study design. Methods: One million people insured under the Taiwan’s National Health Insurance program in 2005 were randomly sampled to create the study’s dataset. According to the presence of cancer and/or stroke, patients were separated into cancer and stroke, cancer-only, and stroke-only groups. Diagnoses of cancer, stroke, and comorbidities were defined according to ICD9-CM codes. Cancer and noncancer populations were matched by age at cancer diagnosis, gender, and stroke risk factors, and each patient with cancer was matched with two noncancer controls nested in the same year of cancer diagnosis. The hazards of stroke and cumulative incidences within a year after cancer diagnosis were evaluated using Fine and Gray’s subdistributional hazard model. Results: The temporal distribution of first-ever stroke in patients with both cancer and stroke was a sharpened bell shape that peaked between 0.5 years before and after cancer diagnosis. Frequencies of stroke were further adjusted by number of cancer survivors. The monthly event rate of stroke remained nested around the time of cancer diagnosis in all strokes. Overall, the cumulative stroke rates in patients with cancer were higher than those in the noncancer matched controls. Conclusions: Cancer increased the risk of stroke and stroke events were nested around the time of cancer diagnosis, occurring 0.5 years prior to cancer on average regardless of stroke type.